Implementasi Model Pembelajaran Jigsaw dalam Proses Pembelajaran Informatika pada Materi Integrasi Aplikasi Perkantoran bagi Siswa Kelas X SMAN 9 Padang - Indra Wijaya; Yuliawati Yunus; Khairunnisa, Afifah; Asiah Siregar; Nesya Hizratul Azkia (Global Action and Education for Society, 2026)
Informatics learning at the upper-secondary level requires instructional strategies that effectively develop students’ technical and collaborative skills, particularly in office application integration, a topic that demands strong procedural accuracy and conceptual understanding. This study aims to describe the implementation of the Jigsaw learning model in Informatics instruction and analyze its effectiveness in improving Grade X students’ understanding of office application integration at SMAN 9 Padang. A descriptive research design was employed, with data collected through classroom observation, project-based document integration assessment, and student response questionnaires. The learning process involved forming home groups and expert groups, allowing each student to master a specific subtopic before teaching it back to their home group members. The findings indicate that the Jigsaw model enhances academic participation, fosters active discussion, and improves students’ ability to produce integrated documents accurately and consistently. Most students achieved mastery learning and demonstrated proficiency in integrating data, graphs, and text according to competency standards. Student responses also revealed that the Jigsaw approach facilitated understanding, as peer explanations and intensive hands-on practice made complex procedures more accessible. Overall, the results confirm that the Jigsaw model is highly relevant for Informatics learning and supports the aims of the Merdeka Curriculum, which emphasizes active, collaborative, and competency-based learning.